NMR investigation on gas desorption characteristics in CBM recovery during dewatering in deep and shallow coals. (18th January 2023) - Sun, Yingfeng; Lin, Qingxia; Zhu, Shuaipeng; Han, Chujian; Wang, Xiaoliang; Zhao, Yixin
Abstract: Coalbed methane (CBM) development requires dewatering until the reservoir pressure is less than the critical desorption pressure. Significant quantities of CBM in China are buried >1000 m deep. Therefore, the desorption characteristics of deep CBM reservoirs must be investigated for the further development of deep CBM. In this study, the variation laws of adsorbed and free CH4 during adsorption in dry samples and during desorption via dewatering are investigated using nuclear magnetic resonance. During CH4 adsorption in dry samples by increasing CH4 pressure and during CH4 desorption in water-injected samples by dewatering, a Langmuir relationship exists between the volume of adsorbed CH4 and the pressure in deep and shallow coals, and the volume of free CH4 and the pressure are linearly related. When the pressure is the same, the volume of adsorbed CH4 in the dry coal samples during adsorption is larger than that in the water-injected samples during desorption by dewatering. When the pressure is the same, for the difference in the adsorbed CH4 volume between adsorption and desorption isotherms, shallow coal is less significant than deep coal. The slopes of free CH4 in deep coal are lower than those in shallow coal during adsorption and desorption.